Vagus Nerve Stimulation Enhances Extinction of Conditioned Fear in Rats and Modulates Arc Protein, CaMKII, and GluN2B-Containing NMDA Receptors in the Basolateral Amygdala - Alvarez-Dieppa, Amanda C. (Neural Plast, 2016)
Vagus nerve stimulation (VNS) enhances the consolidation of extinction of conditioned fear. High frequency stimulation of the infralimbic cortex (IL) produces long-term potentiation in the basolateral amygdala (BLA) in rats given VNS-paired extinction training, whereas the same stimulation produces long-term depression in sham-treated rats. The present study investigated the state of synaptic plasticity-associated proteins in the BLA that could be responsible for this shift. Male Sprague-Dawley rats were separated into 4 groups: auditory fear conditioning only (fear-conditioned); fear conditioning + 20 extinction trials (extended-extinction); fear conditioning + 4 extinction trials paired with sham stimulation (sham-extinction); fear conditioning + 4 extinction trials paired with VNS (VNS-extinction). Freezing was significantly reduced in extended-extinction and VNS-extinction rats. Western blots were used to quantify expression and phosphorylation state of synaptic plasticity-associated proteins such as Arc, CaMKII, ERK, PKA, and AMPA and NMDA receptors. Results show significant increases in GluN2B expression and phosphorylated CaMKII in BLA samples from VNS- and extended-extinction rats. Arc expression was significantly reduced in VNS-extinction rats compared to all groups. Administration of the GluN2B antagonist ifenprodil immediately after fear extinction training blocked consolidation of extinction learning. Results indicate a role for BLA CaMKII-induced GluN2B expression and reduced Arc protein in VNS-enhanced extinction.